A Highly Sensitive and Selective Probe for the Colorimetric Detection of Mn(II) Based on the Antioxidative Selenium and Nitrogen Co-Doped Carbon Quantum Dots and ABTS•+ - Xu, Qinhai; Liu, Xiaolin; Jiang, Yanglin; Wang, Peng (Frontiers in Chemistry, 2021)
Herein, selenium and nitrogen co-doped carbon quantum dots (Se/N-CQDs) were hydrothermally synthesized by using citric acid, histidine and sodium selenite, which had crystalline carbon structure containing sp3 and sp2 bonds and showed the excitation-dependent fluorescence behavior. Furthermore, due to the redox reaction of ABTS•+ and Se/N-CQDs, Se/N-CQDs had the excellent antioxidant capacity that it was demonstrated by scavenging ABTS•+ with the fading of blue. Based on the synergistic effect of Se/N-CQDs and Mn(II) on ABTS•+, Se/N-CQDs and ABTS•+ as a stable, sensitive, selective and reproducible colorimetric sensor was applied to the detection of Mn(II) with a detection limit of 1.69 μM and a linear range of 0 to 142.90 μM. More importantly, the probe was successfully applied to detecting Mn(II) in tap water, illustrating that it could be a promising tool for the Mn(II) detection in water environments.